ret/PTC-1 expression alters the immunoprofile of thyroid follicular cells. - Denning, K; Smyth, P; Cahill, S; Li, J; Flavin, R; Aherne, S; O' Leary, J; Sheils, O (2008)
BACKGROUND: Hashimoto Thyroiditis (H.T.) is a destructive autoimmune thyroid condition whose precise molecular pathogenesis remains unclear. ret/PTC-1 is a chimeric transcript which has been described in autoimmune thyroid disease (AITD) and thyroid neoplasia. The purpose of this study was to observe the immunogenic effect exposure to H.T. and control lymphocyte supernatant would have on normal (Nthy-ori) and ret/PTC-1 (TPC-1) expressing thyroid cell line models. RESULTS: A 2 x 2 matrix comprising Nthy-ori and TPC-1 cell lines and H.T. and control lymphocyte supernatant was designed and utilised as follows; activated lymphocytic supernatant from a H.T. and normal control were co-cultured with a cell line derived from normal thyroid (Nthy-ori) and also a cell line derived from a papillary thyroid carcinoma that endogenously expresses ret/PTC-1 (TPC-1). The co-cultures were harvested at 0, 6 and 18 hour time points. Gene expression analysis was performed on RNA extracted from thyrocytes using TaqMan Immune profiling Low-Density Arrays (Applied Biosystems, CA, USA) comprising gene expression markers for 93 immune related targets plus 3 endogenous controls. Stimulation of the normal thyroid cell line model with activated T cell supernatant from the H.T. donor yielded global up-regulation of immune targets when compared with control supernatant stimulation. In particular, a cohort of targets (granzyme B, CD3, CD25, CD152, CD45) associated with cytotoxic cell death; T cell receptor (TCR) and T cell signaling were up-regulated in the normal cell line model. When the ret/PTC-1 expressing thyroid cell line was co-cultured with H.T. lymphocyte supernatant, in comparison to control supernatant stimulation, down-regulation of the same subset of immune targets was seen. CONCLUSION: Co-culturing H.T. lymphocyte supernatant with a normal thyroid cell line model leads to over-expression of a subset of targets which could contribute to the pathogenesis of H.T. via cytotoxic cell death and TCR signalling. Stimulation of the ret/PTC-1 positive cell line with the same stimulus led to a down-regulated shift in the gene expression pattern of the cohort of immune targets. We hypothesize that ret/PTC-1 activation may dampen immunogenic responses in the thyroid, which could possibly facilitate papillary thyroid carcinoma development.